The influence of providing perches and string on activity levels, fearfulness and leg health in commercial broiler chickens. (2nd December 2014) - Bailie, C. L.; O'Connell, N. E.
Abstract : The aim of this study was to assess the effect of providing environmental enrichment in the form of perches and string on the behaviour and welfare of commercial broiler chickens. Houses containing ~23 000 broiler chickens were assigned to one of four treatments in a 2×2 factorial design. Treatments involved two levels of access to perches (P) (present (24/house) '+P' or absent '−P') and two levels of access to string (S) (present (24/house) '+S' or absent '−S'). All houses contained windows, and 30 straw bales were provided from day 10 of the rearing cycle. Treatments were applied in one of four houses on a single farm, and were replicated over four production cycles. Behaviour and leg health were observed in weeks 3 to 5 of the rearing cycle. Production performance and environmental parameters were also measured. There was an interaction between perches and age in the percentage of birds observed lying, with higher percentages of birds observed lying in the +P treatment than in the −P treatment during weeks 4 and 5. There was also a significant interaction between string and age in the percentage of birds observed in locomotion, with higher percentages observed in locomotion in the −S treatment than in the +S treatment during weeks 4 and 5. There was also an interaction between string and age in average gait scores, with lower gait scores in the +S treatment than in the −S treatment during weeks 3 and 5 but not within week 4. Daytime observations showed that perches and strings were used frequently, with one bout of perching occurring approximately every 80 s/perch, and one bout of pecking at string occurring every 78 s/string on average. There was a significant effect of age on use of perches ( P <0.001) and string ( P <0.001), with perching peaking during week 5 and string pecking peaking during week 3. We conclude that commercial broilers in windowed houses with access to straw bales display an interest in additional enrichment stimuli in the form of perches and string, and therefore that these stimuli have the potential to improve welfare. In addition, provision of string as a pecking device appeared to positively influence walking ability. However, this effect was numerically small, was only shown in certain weeks and was not reflected in the other leg health measure (latency to lie). The results also showed an apparent negative effect of string and perches on the activity levels of birds (recorded away from the immediate vicinity of these enrichments) towards the end of the production cycle. These results emphasise the need for further research into optimum design and layout of enrichment stimuli for modern broilers in windowed houses to ensure that their provision leads to clear welfare benefits.